ANALYSIS OF DETERMINANTS OF INCOME SMOOTHING PRACTICES - Nur Krisnaeni; Djusnimar Zultilisna; Siska Priyandani Yudowati (JASS (Journal of Accounting for Sustainable Society), 2022)
Income. smoothing is a corporate. Management.'s effort to reduce the. volatility of financial statements to make them more attractive to investors. This is usually done by manipulating. financial statements, especially in the income statement section.This study aims to understand the impact of profitability, financial leverage, income tax, and winner/loser stocks on the income smoothing of financial industry companies in the banking sub-industry listed on the Indonesian Stock Exchange from 2016 to 2019. This study uses quantitative research and purpose-based sampling techniques to collect data. There have been 22 companies as samples for more than four years, resulting in 88 research samples. Data processing uses SPSS 25.0 application for descriptive statistical and logistic regression analysis. This. study shows that profitability, financial leverage, income tax, and. winner/loser have simultaneous impact on income smoothing. Profitability has a partial positive impact and income tax has a partial negative impact on income smoothing. While financial leverage and winner/loser stocks do not affect the income smoothing.